Interpretation of the results of the technical indicators of agriculture-specific economic - Victor Olteanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
The passage of a technological process is carried out only in circumstances where the process is efficient in economic terms. Assessment of technological processes can be done by means of indicators which can be: economic, technical, economic and technical. Technical-economic indicators used in assessing technological processes are scalars with or without dimensions, which characterizes a substance, a technical device, a system, or a technological process both technically and economically.
Keywords: 330; system technology; agricultural establishments; financial statements